Pengaruh Disiplin Kerja Dalam Meningkatkan Produktivitas Kerja Karyawan Pada PT. BHB (Batang Hari Barisan) Padang By Pass Kelurahan Batuang Taba Lubuk Begalung - Dista, Putri Buolqis; Jhon Rinaldo; Novi Yanti (Ekasakti Matua Jurnal Manajemen, 2023)
PT. BHB (Batang Hari Barisan) Padang By Pass Batuang Village Taba Lubuk Begalung is a rubber factory company. The amount of rubber production from 2016 - 2020 fluctuated where the amount was unstable, it was seen that it changed every year. The purpose of the study was to determine the effect of work discipline in increasing employee productivity at PT. BHB (Batang Hari Barisan) Padang BY PASS Batuang Taba Village, Lubuk Begalung. Data collection methods are Field Research (Field Research) and Library Research (Library Research). The types and sources of data are primary data and secondary data. The population of this research is all office employees at PT. BHB as many as 272 people. and a sample of 73 people. The analytical method used is simple linear regression analysis. The results of simple linear regression analysis and partial hypothesis testing (t test) show that there is a positive and significant effect on work discipline which has a significant effect on employee work productivity at PT. BHB (Batang Hari Barisan) Padang By Pass, Batuang Taba Village, Lubuk Begalung.